Penerapan Model Induktif Berbantuan Media Wayang Suket pada Siswa Sekolah Dasar - Meidawati Suswandari (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2018)
The purpose of this study is to analyze the application of inductive learning models assisted by wayang suket (mikayet) media to improve learning motivation in fourth grade students of SD N 03 Palur, Sukoharjo. This study uses experimental research. The research design used was pretestposttest control group design. The experimental group is class IV b using an inductive model assisted by wayang suket media, while the control group is class IV a using the lecture and question and answer method without learning media. Data collection techniques using questionnaires and documentation. Data analysis techniques usehypothesis testing. The results showed that the application of assisted inductive learning models in wayang suket (mikayet) media could increase learning motivation in fourth grade students of SD N 03 Palur, Sukoharjo. This can be seen in the difference in scores of students' learning motivation significantly in the experimental class compared to the control class. Based on the post-test t test, it is known that the average learning motivation of the experimental class is 20.00 and the average of the control class learning motivation is 18.18, so it can be concluded that the average experimental class learning motivation is 1.88 greater than control class.